GAMBARAN PEMBERDAYAAN PSIKOLOGIS DAN KINERJA TENTOR DI LBB GRIYA TALENTA SURABAYA - Risma Nur Avita; Adhystia Putri; Sayla Rahmatillah; Xena Puspita; Saarah Alya (PSIKOWIPA (Psikologi Wijaya Putra), 2022)
This study aims to determine the description of psychological empowerment and its impact on the performance of LBB tutors. The sample used in this study was an employee or tutor of the Griya Talenta Surabaya Tutoring Institute. This research method uses interviews as a research instrument. The analysis used in this research is PFD analysis. The results showed that subject A had four dimensions of psychological empowerment, namely, meaning, competence, self-determination, and impact. There are efforts to empower and improve the ability of the tutors at Griya Talenta Bunda Surabaya, namely the holding of training once a year. Forms of training related to microteaching, holding FGDs, and group tutors to improve teaching skills, problem solving skills, and increase confidence in tutors so that tutors can display optimal performance.